Seasonal Variation, Chemical Composition and Antioxidant Activity of Brazilian Propolis Samples. Issue 3 (2010) - Teixeira, Érica Weinstein; Message, Dejair; Negri, Giuseppina; Salatino, Antonio; Stringheta, Paulo César
Abstract : Total phenolic contents, antioxidant activity and chemical composition of propolis samples from three localities of Minas Gerais state (southeast Brazil) were determined. Total phenolic contents were determined by the Folin–Ciocalteau method, antioxidant activity was evaluated by DPPH, using BHT as reference, and chemical composition was analyzed by GC/MS. Propolis from Itapecerica and Paula Cândido municipalities were found to have high phenolic contents and pronounced antioxidant activity. From these extracts, 40 substances were identified, among them were simple phenylpropanoids, prenylated phenylpropanoids, sesqui- and diterpenoids. Quantitatively, the main constituent of both samples was allyl-3-prenylcinnamic acid. A sample from Virginópolis municipality had no detectable phenolic substances and contained mainly triterpenoids, the main constituents being α- and β-amyrins. Methanolic extracts from Itapecerica and Paula Cândido exhibited pronounced scavenging activity towards DPPH, indistinguishable from BHT activity. However, extracts from Virginópolis sample exhibited no antioxidant activity. Total phenolic substances, GC/MS analyses and antioxidant activity of samples from Itapecerica collected monthly over a period of 1 year revealed considerable variation. No correlation was observed between antioxidant activity and either total phenolic contents or contents of artepillin C and other phenolic substances, as assayed by CG/MS analysis.